PENGARUH MEDIA PUZZLE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS III SDN 3 AMPENAN - Adelia, Irna; Musaddat, Syaiful; Hasnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Problem solving ability is one part of the cognitive domain aspect. Considering that elementary school age children need to overcome the difficulties they will face, children must have problem-solving skills to solve problems in everyday life. Learning wing be more fun if children are thaught using puzzle media where children will learn to solve problem by putting together parts or pieces of the puzzle. The aim of this research is to determine the effect of puzzle media on children’s mathematical problem solving abilities. The type of research used is quasi experimental research. The population in this study was class III students at SDN 3 Ampenan, sampling as carried out using a saturated sampling technique which took a total population of 51 students. Class III A as the control class and III B as the experimental class. Data collection techniques are by means of observation and tests. Data analysis was carried out using an independent samples T test with prerequisite tests using normality and homogeneity tests. The prerequisite test results show that the data is normally distributed with pretest and posttest scores in both classes > 0.05 and homogeneous data (0.09 > 0.05). As for the hypothesis test, the tcount value was 2,247 > ttable 1,677 and Sig.2 tailed < 0.05, namely 0.03 < 0.05. So it can be concluded that there is an influence of the use of puzzle media on the mathematical problem solving abilities of class III students at SDN 3 Ampenan.